Analysis of Antecedents Variables of Financial Behavior Intention: An Empirical Study - Rahma, Stephanie; Chandra, Novi; Sihombing, Sabrina (Master of Management Diponegoro University, 2020)
This research aims to examine relationship between antecedents’ variables of financial behavior intention. This research involves 350 respondents which were collected through online questionnaire. Data was examined by reliability and validity tests before hypotheses testing. Hypotheses testing were applied by using structural equation modeling. All research hypotheses were supported except the hypothesis that stated the relationship between perceived control and financial behavior intention. This research provides discussion, conclusion, limitations and recommendation for future research.